Are there possible associations between MnSOD and GPx1 gene variants for laryngeal cancer risk or disease progression? - Coskun, C; Verim, A; Farooqi, A A; Turan, S; Mezani, B; Kucukhuseyin, O; Tolgahan Hakan, M; Ergen, A; Yaylim, I (Cellular and Molecular Biology, 2016)
Laryngeal squamous cell carcinoma (LSCC) is a multifaceted and genomically complex disease and cellular and preclinical studies have demystified wide ranging molecular mechanisms which underpin its development and progression and resistance against wide ranging molecular therapeutics. Oxidative stress is a widely studied molecular mechanism and reportedly involved in carcinogenesis. Increasingly it is being realized that accumulation of Reactive Oxygen Species (ROS) activates defensive mechanism to counteract oxidative stress induced damage. Manganese superoxide dismutase (MnSOD) and glutathione peroxidase (GPx) are important members of defensive machinery. We investigated whether the polymorphisms of MnSOD (Ala-9Val, rs4880) and GPx1 (Pro198Leu, rs1050450) are associated with LSCC and also evaluated possible interactions between these polymorphisms and various lifestyle factors or pathological features of patients. For this purpose, 67 LSCC patients and 73 healty controls were enrolled. Molecular assessment of MnSOD and GPx1 variants were determined with polymerase chain reaction-restriction fragment length polymorphism techniques. We found that the frequency of both heterozygous PL genotype and P allele was considerably higher in patients with advanced tumor stage (T3/T4) than in those with early tumor stage (T1/T2) (OR= 5.106; 95% CI=1.372-19.004; p<0.001, OR=5.787; 95% CI =1.564-21.414; p<0.001 respectively). Although the frequency of ValVal/LL combine genotype was significantly decreased (OR=0.204, 95% CI=0.055-0.760; p=0.021), the frequency of ValAla/PL combine genotypes was higher in patients with stage T3/T4 than in those patients with stage T1/T2 (p=0.027). Consequently, we have concluded that variants of GPx1 and MnSOD should not be considered as a risk factor of LSCC, only may be accepted as a prognostic markers. Use of new technologies such as metabolomics and deep DNA sequencing will prove to be helpful in developing a deeper knowledge related to how cancer cell metabolism adapts and provides a buffer against increased oxidative stress.